Analysis of Methods of Discovery of Islamic Law: A Critical Study of Qiyas, Al-Maslahah Al-Mursalah, Istihsan, and Al-Urf in a Contemporary Context - Solihan Makruf; Rizal Agung Mufti; Diding Jalaludin; Lis Diana Ningsih; Ramdani Wahyu Sururie (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to evaluate the application of Islamic legal research methods, namely qiyas, al-maslahah al-mursalah, istihsan and al-'urf, in responding to contemporary legal issues in Indonesia. The research method used is a literature review by analysing classical and modern sources of Islamic law, including books, scholarly journals, and relevant fatwas and legal regulations. The results show that the four methods can be flexibly applied to resolve modern legal issues such as early marriage, the status of children in Siri marriages and domestic violence. The contribution of this research is to provide an integrative and dynamic approach to the development of Islamic law, so that it can provide relevant solutions to contemporary legal challenges and support the integration of Islamic law into the national legal system.